(untitled) (Economic and Political Thought, 2012)
Greece is one of the Eurozone countries that have been severely stricken with public debt crisis since 2009. Without the financial help from the European Union and the International Monetary Fund, Greece would not be able to repay its debts to the creditors. The condition for providing aid to this country was that Greece commits itself to a macroeconomic program aimed at stabilizing public finance and regaining the capability of raising funding resources on the financial markets on its own. The practice shows that as a result of the implementation of the program the situation of Greece has not improved at all but worsened. It turned out that it is necessary to restructure the Greek public debt and this may lead to considerable losses for the investors. The possible results of such restructuring for Greece as well as the Eurozone and other European Union countries, including Poland, are very difficult to predict. The first tranche of the bailout program for Greece proved to be ineffective in solving the problem of its public debt.